Nutrition and Antioxidant Potential of Three Cauliflower (Brassica oleracea L. Var. Botrytis) Cultivars Cultivated in Southern Part of Bangladesh - Mousumi Jahan Sumi; Sharmin Akter Serity; Tusar Kanti Roy; Keya Akter; Shishir Rasul; Mostofa Jaman Depro; Md. Masum Abdullah; Md. Nesar Uddin (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to evaluate the biochemical and nutritional profiles of three cauliflower cultivars—Valentena, Carotena, and Snow White—focusing on chlorophyll, carotenoids, anthocyanins, vitamin C, flavonoids, phenolics, and antioxidant activity. Uniform curds were harvested at 60 days post-sowing from Baratia, Dumuria, Khulna, and analyzed at Khulna Agricultural University. Valentena exhibited the highest chlorophyll content (40.06±0.39 µg/100g FW chlorophyll a, 28.98±3.35 µg/100g FW chlorophyll b), superior lycopene (8.71±0.38 µg/100g FW) levels. Carotena showed the highest total carotenoid content (60.52±1.76 µg/100g FW) and β-carotene (26.99±0.44 µg/100g FW), while Snow White had the lowest values across most parameters. Valentena also led in anthocyanins (101.56±3.9 mg/L FW) and total flavonoids (79.56±10.36 mg/100g FW), with Carotena having the highest vitamin C content (60.05±2.93 µg/g FW). DPPH assays indicated that Valentena showed the most effective antioxidant (IC50 = 43.65±3.56 mg/mL FW), followed by Carotena and Snow White. Hierarchical clustering and pricipal component analysis (PCA) revealed distinct biochemical profiles: Valentena and Carotena shared similarities in carotenoids and antioxidant activity, whereas Snow White differed significantly. Linear discriminant analysis identified lycopene, chlorophyll b, and β-carotene as major differentiators, highlighting the diverse nutritional and antioxidant properties of these cauliflower varieties. The findings highlight the potential of Carotena and Valentena for health-conscious consumers seeking nutrient-rich, antioxidant benefits in functional meals.